Renal angiomyoadenomatous tumor: morphologic, immunohistochemical, and molecular genetic study of a distinct entity - Michal, Michal; Hes, Ondřej; Němcová, Jana; Šíma, Radek; Kuroda, N; Bulimbasic, S; Franco, M; Sakaida, N; Daniš, Dušan; Kazakov, Dmitry V; Ohe, C; Hora, Milan (Virchows Archiv, 2009)
We present a series of a distinct tumorous entity named renal angiomyoadenomatous tumor (RAT). Five cases were retrieved from the consultation files of the authors. Histologic and immunohistochemical features were evaluated. Sequencing analysis of coding region of the VHL gene was carried out in all cases. The tumors were composed of admixture of an epithelial clear cell component and prominent leiomyomatous stroma. Epithelial cells formed adenomatous tubular formations endowed with blister-like apical snouts. All tubular/glandular structures were lined by a fine capillary network. The epithelial component was positive for epithelial membrane antigen, CK7, CK20, AE1-AE3, CAM5.2, and vimentin in all cases. In all analyzed samples, no mutation of the VHL gene was found. RAT is a distinct morphologic entity, being different morphologically, immunohistochemically, and genetically from all renal tumors including conventional clear cell carcinoma and mixed epithelial and stromal tumor of kidney.
Keywords: Vimentin; keratin-20; biologické markery; lidé; Middle Aged; vimentin; Financing, Organized; financování organizované; Keratins; Kidney Neoplasms; Female; Epithelial Cells; Mutation; Loss of Heterozygosity; Mucin-1; Humans; Keratin-7; Adenoma; keratin-7; mutace; nádory ledvin; epitelové buňky; lidé středního věku; Biomarkers; mužské pohlaví; nádorový supresorový protein VHL; keratiny; Von Hippel-Lindau Tumor Suppressor Protein; ženské pohlaví; Aged, 80 and over; mucin 1; senioři nad 80 let; Male; Aged; adenom; Keratin-20; ztráta heterozygozity; senioři